Quality of health care for refugees - a systematic review - Karolin Hahn; Jost Steinhäuser; Denise Wilfling; Katja Goetz (BMC, 2019)
Abstract Objective The aim of this systematic review was to identify quality indicators (QI) developed for health care for refugees. Methods We conducted a systematic review of international QI databases such as the Agency for Health care Research and Quality in addition to a systematic search in PubMed, Cochrane library and Web of Science, using the terms "refugee" and "quality indicator", complemented by a search in reference lists and grey literature. All papers which included QIs for refugees, especially for health care were included. In a first step all existing QIs were screened for their relevance to refugees. In a second step, all health care QIs were extracted. In a final step, these health care QIs were classified into process, structure and outcome indicators. Results Of 474 papers, 23 were selected for a full-text review. Of these 23 publications, 6 contained 115 QIs for health and health care for refugees. The main health care topics identified were reproductive health, health care service and health status. Conclusions Most indicators were indicators for outcome and structure quality, the smallest group were process indicators. Within the area of refugee health care, most QIs that have been found were QIs regarding reproductive health. QI databases do not yet include indicators specifically related to refugees.